Descriptions of final instar larvae of six species of the genus Hydroptila Dalman (Trichoptera, Hydroptilidae) in Japan - Ito, Tomiko (Zootaxa, 2021)
Final instar larvae of six species of the genus Hydroptila Dalman (Trichoptera, Hydroptilidae) belonging to three species groups are described based on Japanese specimens. These are H. phenianica Botosaneanu 1970, H. dampfi Ulmer 1929 and H. oguranis Kobayashi 1974 of the H. pulchricornis Species Group, H. kakidaensis Nozaki & Tanida 2007 and H. botosaneanui Kumanski 1990 of the H. tineoides Species Group, and H. nanseiensis Ito 2011 (in Ito et al. 2011), which is unplaced to species group. They can be distinguished from each other by the color patterns of the head and thoracic nota, relative lengths of the longest head setae to the width of the head, and number of setae on the thorax. For discrimination of species groups, the arrangement of chloride epithelia of abdominal segments is likely to be useful, since it differs in the three species groups studied here.